The AMA handbook of financial risk management - Hampton, John J., 1942- (American Management Association, 2011)
Because all business is risky business. Managing financial risk boils down to understanding how to reduce a complex business environment into workable concepts and models. The AMA Handbook of Financial Risk Management provides readers with the tools they need for dealing with the most important areas of financial decision making. Filled with strategies, principles, and measurement techniques, the book shows readers how to: ò Categorize financial risks ò Reduce risks from cash flow and budget exposures ò Analyze operating risks ò Understand the interrelationship of risk and return ò Manage risk.